2022
DOI: 10.1177/03635465221120654
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Ulnar Collateral Ligament Surgery in Nonthrowing Athletes

Abstract: Background: Ulnar collateral ligament (UCL) surgery continues to demonstrate excellent clinical outcomes and a high return-to-play (RTP) rate with a low complication rate. Recent studies have demonstrated similar clinical outcomes for baseball players who have undergone either UCL reconstruction or UCL repair. In comparison, few studies have assessed the clinical outcomes of UCL surgery for nonthrowing athletes. Purpose/Hypothesis: The primary objective of this study is to provide clinical outcomes of UCL surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
2
0
3
Order By: Relevance
“…11 More recent data from Dugas and colleagues has argued that overhead-throwing and nonthrowing athletes may benefit from acute primary repair of the distal UCL, which should be of consideration when evaluating these patients. 13,14 Of note, none of our patients underwent primary distal UCL repair. When surgery was performed to address injury at the sublime tubercle, management consisted of UCL reconstruction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…11 More recent data from Dugas and colleagues has argued that overhead-throwing and nonthrowing athletes may benefit from acute primary repair of the distal UCL, which should be of consideration when evaluating these patients. 13,14 Of note, none of our patients underwent primary distal UCL repair. When surgery was performed to address injury at the sublime tubercle, management consisted of UCL reconstruction.…”
Section: Discussionmentioning
confidence: 94%
“…The authors concluded that operative management was warranted in treating sublime tubercle avulsion injuries to return these patients to asymptomatic preinjury level of activity.11 Notably, initial nonsurgical management in this cohort consisted of immobilization in a range of motion brace locked at 90 degrees for 7 to 10 days, followed by 6 weeks of brace wear in an unlocked position 11 . More recent data from Dugas and colleagues has argued that overhead-throwing and nonthrowing athletes may benefit from acute primary repair of the distal UCL, which should be of consideration when evaluating these patients 13,14 . Of note, none of our patients underwent primary distal UCL repair.…”
Section: Discussionmentioning
confidence: 95%
“…Die durchschnittliche Rückkehr zum Sport dauerte nur 6,7 Monate, was deutlich kürzer war als bei herkömmlichen Rekonstruktionsverfahren. Eine weitere Untersuchung von Rothermich et al zeigte bei nicht werfenden Athleten eine Rückkehr zum Sport von etwa 93 % nach durchschnittlich 7,4 Monaten 54 . Nach der Behandlung von mehr als 350 Athleten mit MUCL-Naht und interner Brace-Augmentation legten Wilk et al einen Rehabilitationsplan vor, der es den Athleten ermöglichte, nach etwa 5 Monaten wieder zu spielen 67 .…”
Section: Operative Versorgungunclassified
“…Nach der Behandlung von mehr als 350 Athleten mit MUCL-Naht und interner Brace-Augmentation legten Wilk et al einen Rehabilitationsplan vor, der es den Athleten ermöglichte, nach etwa 5 Monaten wieder zu spielen 67 . Rothermich et al berichten von exzellenten 2-Jahres-Ergebnissen auch bei Nichtwurfsportlern im American Shoulder and Elbow Surgeons (ASES) Score mit durchschnittlich 94,4 Punkten nach Internal Bracing des MUCL bei einer RTS-Rate von 93 % und einer RTS-Dauer von durchschnittlich 7,4 Monaten 54 . Die Komplikationsrate nach Internal Bracing des MUCL beträgt 11,9 % 53 .…”
Section: Operative Versorgungunclassified
See 1 more Smart Citation